Pseudomonas fluorescens and its effect on blueberry (Vaccinium spp.) tolerance to phytopatogenic fungi (Bioagro, 2026)
Blueberry is a relative new crop in Mexico, it has been cultivated since the early 2000s; however, in the field it presents fruit worm, trips, and diseases caused Alternaria, Botrytis, Fusarium,Pestalotia y Phytophthora. This research shown the effect of in vitro inhibition of Pseudomonas fluorescens UM16, UM240, UM256, and UM270 strains against pathogenic fungi Phytophtora cinnamomi, Fusarium sp., and Phomopsis vaccinii, and the inoculation of Pseudomonas and fungi on blueberry (Vaccinium spp.) genotypes, Biloxi and UM811. The inhibition tests showed that the strains UM270, UM16, and UM256 inhibited Phytophtora cinnamomi, and Fusariu sp. by 34 and 30 % respectively, but not Phomopsis vaccinii. The Biloxi plants inoculated with the strains UM270, UM16+Phytophtora, and UM16+Phomopsis showed greater plant length with 91,6, 90,1 and 90,8 cm, respectively, greater dry root weight with 43,5 g (UM256+Phomopsis) and plant dry weight with 31,5 g, (UM16+Phomopsis), comparated with the UM811 genotype con45,3 cm (UM240+Fusarium), 43 g (UM240), and 15,1 g (UM240+Phomopsis), respectively, and the control plants of each genotype. The results showed that Pseudomonas strains used in this research can be a viable alternative in the control of  Fusarium  and Phytophtora root fungi , in blueberry crop.
Keywords: Inhibition; phytopathogenic fungi; Pseudomonas fluorescens